APLIKASI POT BAMBU SEBAGAI MEDIA REHABILITASI HABITAT MANGROVE KAWASAN PESISIR DI PANGA ACEH JAYA - Setiadi M Noor; Ilham Muryanto; Dafliamansyah Halawa; Silfia Ramadia; Syahrul Muhharram; Muhammad Rizal (Universitas Teuku Umar, 2022)
Mangrove is a pioneer plant that grows and develops on the coast and becomes the main wave barrier in coastal areas (Woodroffe et al.2016). Based on WIIP and WWF data through the Green Coast program, since 2005 the rehabilitation process of mangrove populations has been conducted in Aceh Jaya Regency. Based on mangrove rehabilitation through gerhan projectdata, an area of 2550 hectares of mangrove area in the west coast area has been rehabilitated since 2005. Socialization and Education of bambu pot application method contributes greatly to the people of Aceh, especially those on the coast of Keude Panga Aceh Jaya. The potential results of socialization/education activities are as follows:1. Mangrove conservation education and mangrove socialization by bambu pot method to partners and local communities change the mindset about mangroves that have many benefits for life .2. With the knowledge that has been given, it is expected that the community can better maintain and preserve mangroves from damage 3. The younger generation and the community can continue their activities with the Organization of coastal conservation teams that have been formed by the Team, it is expected that there is sustainability from the community.The stages that are improved are strengthening the institutions that have been formed through study clubs and partner mentoring.